PENGARUH MANAJEMEN STRES DAN MANAJEMEN WAKTU TERHADAP PRODUKTIVITAS AKADEMIK MAHASISWA PENDIDIKAN EKONOMI (Survei Mahasiswa Pendidikan Ekonomi Universitas Siliwangi Angkatan 2022-2023) - Melani Novitasari; Astri Srigustini; Kurniawan Kurniawan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of stress management and time management on academic productivity through a survey of Economic Education students from the 2022 and 2023 cohorts at Siliwangi University. This research employed a survey method with a quantitative approach. The sampling technique used was probability sampling through simple random sampling, involving a total of 160 student respondents. The data were collected using a questionnaire, while the data analysis technique applied multiple linear regression analysis. The results showed that stress management had a positive and significant effect on students’ academic productivity, time management had a positive and significant effect on students’ academic productivity, and both stress management and time management simultaneously had a positive and significant effect on the academic productivity of Economic Education students at Siliwangi University.